The Effect of Tonsillectomy and Adenoidectomy on Upper Airway Obstruction Patterns in Children with Obstructive Sleep Apnea - Mothersole, Kelsey; Ulualp, Seckin Omer; Szmuk, Peter; Liu, Christopher (International Archives of Otorhinolaryngology, 2023)
Introduction Alterations in upper airway flow dynamics and sites of airway obstruction immediately after tonsillectomy and adenoidectomy (TA) have not been assessed. Identification of the changes in airway obstruction patterns after TA potentially improves the surgical management of children with obstructive sleep apnea (OSA).Objective To evaluate the effect of TA on upper airway obstruction patterns detected with drug-induced sleep endoscopy (DISE).Methods The medical records of patients who underwent pre-TA DISE during the induction of anesthesia and post-TA DISE at the end of TA were reviewed. Data pertaining to polysomnography and DISE findings were analyzed.Results Twenty-seven patients (15 male and 12 females aged between 2 and 18 years old) were identified. All patients had obstruction at multiple sites of the upper airway. Prior to TA, airway obstruction was at the level of the velum in 27 patients, of the oropharynx/lateral walls in 27, of the tongue in 7, and of the epiglottis in 4. After TA, airway obstruction was at the level of the velum in 24 patients, of the oropharynx/lateral walls in 16, of the tongue in 6, and of the epiglottis in 4. The degree of obstruction at the levels of the velum and oropharynx/lateral walls after TA was significantly decreased.Conclusions Drug-induced sleep endoscopy performed prior to TA revealed that most of the sites of airway obstruction persisted after TA in OSA children with multiple sites of airway obstruction. Further studies in larger group of children with OSA are needed to establish the value of DISE findings in predicting residual OSA after TA, surgical planning, determining the need for post TA sleep study, and counseling caregivers.
Keywords: airway obstruction; drug-induced sleep endoscopy; obstructive sleep apnea; tonsillectomy